2011
DOI: 10.1208/s12248-011-9279-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Targets of Azadirachta indica Associated with Inhibition of Tumor Growth in Prostate Cancer

Abstract: Advanced prostate cancer has significant long-term morbidity, and there is a growing interest in alternative and complimentary forms of therapy that will improve the outcomes of patients. Azadirachta indica (common name: neem) contains multiple active compounds that have potent anti-inflammatory and anticancer properties. The present study investigates the novel targets of the anticancer activity of ethanol extract of neem leaves (EENL) in vitro and evaluates the in vivo efficacy in the prostate cancer models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 46 publications
3
40
0
Order By: Relevance
“…In addition, the fractions also inhibited the activities of both COX-1 and COX-2, the enzymes essential for the prostaglandin synthesis (Kirkby et al, 2013). These findings are in agreement with some earlier reports on the in vitro inhibition of IL-1 and TNF-a production by neem extracts (Alam et al, 2012;Kaur et al, 2004;Mahapatra et al, 2011). However, a confirmatory in vivo test was imperatively needed to double check the observed in vitro effects, since the synthesis of cytokines in vivo may be affected by different physiological factors that are usually not present under in vitro conditions (Petrovsky & Harrison, 1995).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the fractions also inhibited the activities of both COX-1 and COX-2, the enzymes essential for the prostaglandin synthesis (Kirkby et al, 2013). These findings are in agreement with some earlier reports on the in vitro inhibition of IL-1 and TNF-a production by neem extracts (Alam et al, 2012;Kaur et al, 2004;Mahapatra et al, 2011). However, a confirmatory in vivo test was imperatively needed to double check the observed in vitro effects, since the synthesis of cytokines in vivo may be affected by different physiological factors that are usually not present under in vitro conditions (Petrovsky & Harrison, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…The anti-apoptotic, anti-proliferative, and immunomodulatory effects of the herb are reported (Kaur et al, 2004;Mahapatra et al, 2011;Schumacher et al, 2011), implying a potential anti-inflammatory activity. Several independent studies indicated the basic and preliminary evidences in support of its anti-inflammatory activity (Manogaran et al, 1998;Okpanyi & Ezeukwu, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Neem is an omnipotent tree and as acrid gift of nature. The A. indica is a very useful traditional medicinal plant in the African sub-continent and each part of the tree has some medicinal properties [19,1,8]. Neem tree is a tree in the mahogany family Meliaceae, is evergreen tree found in most tropical countries.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary metabolites are used for medicine, flavourings and recreational drugs. These compounds after possible chemical manipulation provide and improved drugs to treat the infectious diseases [19].…”
Section: Introductionmentioning
confidence: 99%
“…Increase in expression levels of HMOX1, AKR1C2, AKR1C3, and AKR1B10 was observed in prostate cancer cells after treatment with an ethanolic extract of neem leaves (Mahapatra et al, 2011). Inhibition of PC-3 cell proliferation and Bcl-2 expression was observed after neem treatment (Priyadarsini et al, 2009).…”
Section: Signaling Molecules That Mediate the Biological Effects Of Hmentioning
confidence: 97%